Coating of chitosan on poly D,L-lactic-co-glycolic acid thymoquinone nanoparticles enhances the anti-tumor activity in triple-negative breast cancer - Gao, Jingrong; Kumari, Ankita; Zeng, Xin-An; Chan, Siewyin; Farooq, Muhammad Adil; Alee, Mahafooj; Khan, Shaheer Hasan; Rahaman, Abdul; He, Shan; Xin, Xiong; Mehmood, Tariq (Frontiers in Chemistry, 2023)
Breast cancer is the second most common cancer around the world. Triple-negative breast cancer (TNBC) is characterized by the absence of three receptors: progesterone, estrogen, and human epidermal growth factor-2 receptor (HER2). Various synthetic chemotherapies have gained attention but they caused unwanted side effects. Therefore, some secondary therapies are now becoming famous against this disease. For instance, natural compounds have been extensively researched against many diseases. However, enzymatic degradation and low solubility remain a major concern. To combat these issues, various nanoparticles have been synthesized and optimized from time to time, which increases its solubility and hence therapeutic potential of a particular drug increases. In this study, we have synthesized Poly D,L-lactic-co-glycolic acid (PLGA) loaded thymoquinone (TQ) nanoparticle (PLGA-TQ-NPs) and then coated them by chitosan (CS) (PLGA-CS-TQ-NPs), which was characterized by different methods. Size of non-coated NPs was 105 nm with PDI value of 0.3 and the size of coated NPs was 125 nm with PDI value of 0.4. Encapsulation efficiency (EE%) and Drug loading (DL%) was found to be 70.5 ± 2.33 and 3.38 for non-coated and 82.3 ± 3.11 and 2.66 for coated NPs respectively. We have also analysed their cell viability against MDA-MB-231 and SUM-149 TNBC cell lines. The resultant, nanoformulations exhibit anti-cancerous activity in a dose and time-dependent manner for MDA-MB-231 and SUM-149 cell lines with an IC50 value of (10.31 ± 1.15, 15.60 ± 1.25, 28.01 ± 1.24) and (23.54 ± 1.24, 22.37 ± 1.25, 35 ± 1.27) for TQ free, PLGA-TQ-NPs and PLGA-CS-TQ-NPs respectively. For the first time, we have developed a nanoformulations of PLGA loaded TQ coated with CS NPs (PLGA-CS-TQ-NPs) against TNBC which led to their enhanced anti-cancerous effects.